Fabrication characterization and mechanical properties of gradient triply periodic minimal surface structures via fused deposition modeling - Heng-Liang, Fan; Abdullah, Yassin (Matéria, 2025)
Triply periodic minimal surface (TPMS) structures have gained significant interest due to their excellent mechanical characteristics and diverse range of applications across various fields. This study systematically designs and analyzes uniform and gradient porous structures based on Primitive and Gyroid TPMS geometries. The samples were fabricated using fused deposition modeling (FDM) with polylactic acid (PLA). Their morphologies were characterized via optical microscopy and micro-computed tomography (micro-CT), and quasi-static compression tests were performed under controlled conditions to evaluate their mechanical properties. The results demonstrated that the fabricated pore characteristics closely matched with the design parameters. For the uniform structures, yield strength decreased from 11.26 MPa at 30% porosity to 2.24 MPa at 50% porosity, and the elastic modulus decreased from 309.8 MPa to 167.1 MPa as porosity increased from 30% to 50%. At the same porosity, uniform structures exhibited higher yield strength than gradient structures. Additionally, an empirical equation derived from the Gibson-Ashby model was introduced to predict the compressive behavior of porous structures based on their relative density. These findings provide essential guidance for designing lightweight structures with enhanced mechanical properties, highlighting the potential of TPMS porous structures for advanced engineering applications.